Responses of the coral reef cryptobiome to environmental gradients in the Red Sea. - Rodrigo Villalobos; Eva Aylagas; Joanne I Ellis; John K Pearman; Holger Anlauf; Joao Curdia; Diego Lozano-Cortes; Alejandro Mejia; Florian Roth; Michael L Berumen; Susana Carvalho (PLoS ONE)
An essential component of the coral reef animal diversity is the species hidden in crevices within the reef matrix, referred to as the cryptobiome. These organisms play an important role in nutrient cycling and provide an abundant food source for higher trophic levels, yet they have been largely overlooked. Here, we analyzed the distribution patterns of the mobile cryptobiome (>2000 μm) along the latitudinal gradient of the Saudi Arabian coast of the Red Sea. Analysis was conducted based on 54 Autonomous Reef Monitoring Structures. We retrieved a total of 5273 organisms, from which 2583 DNA sequences from the mitochondrially encoded cytochrome c oxidase I were generated through sanger sequencing. We found that the cryptobiome community is variable over short geographical distances within the basin. Regression tree models identified sea surface temperature (SST), percentage cover of hard coral and turf algae as determinant for the number of operational taxonomic units present per Autonomous Reef Monitoring Structures (ARMS). Our results also show that the community structure of the cryptobiome is associated with the energy available (measured as photosynthetic active radiation), sea surface temperature, and nearby reef habitat characteristics (namely hard corals, turf and macroalgae). Given that temperature and reef benthic characteristics affect the cryptobiome, current scenarios of intensive climate change are likely to modify this fundamental biological component of coral reef functioning. However, the trajectory of change is unknow and can be site specific, as for example, diversity is expected to increase above SST of 28.5°C, and with decreasing hard coral and turf cover. This study provides a baseline of the cryptobenthic community prior to major coastal developments in the Red Sea to be used for future biodiversity studies and monitoring projects. It can also contribute to better understand patterns of reef biodiversity in a period where Marine Protected Areas are being discussed in the region.